Justification of the Rheological Model of Process of Plastic Material Injection by the Rollers (Agricultural Engineering, 2019)
It is justified thatproblems related to the changes in structural and mechanical properties of plastic material and influence of structural elements of equipment and modes of implementation of the for-mation process on them are considered detail, taking into account empirical data, theoretical dependencies and results of physical experiments. It was established that during the mechanical influence of rollers with grooves on a structured dispersion plastic material in the node of injection of the molding machine, internal shear, and shearing deformation have a preponderant value. Accordingly, the productivity of machines is determined mainly by the structural parameters of the working bodies geometry, kinematics, and contact area. It is shown that increasing the pressure in the plastic material causes a decrease in its volume, but the relationship between pressure and volume has a nonlinear character. It has been established that regardless the variety of flour from which the plastic material was prepared for bagels, its moisture content and the duration of fermentation reduced viscosity of the effective plastic material along with the increase of the shear stress. The paper describes the refined rheological model of the Bingham body deformation, which develops instantaneously, and the velocity of the common elastic deformation in the dough is a simultaneous function of stresses and temperatures, which are close to exponential ones.